2018
DOI: 10.2196/ijmr.9554
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Adults’ Use of Facebook and the Potential Impact on Health Behavior: Secondary Data Analysis

Abstract: BackgroundSocial influences are a primary factor in the adoption of health behaviors. Social media platforms, such as Facebook, disseminate information, raise awareness, and provide motivation and support for positive health behaviors. Facebook has evolved rapidly and is now a part of many individuals' daily routine. The high degree of individual engagement and low attrition rate of this platform necessitate consideration for a potentially positive impact on health behavior.ObjectiveThe aim of this paper is to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 14 publications
4
11
0
Order By: Relevance
“…We expect to found a definite influence of demographic variables such as gender and age in the association between functions of AMs and Facebook usage (Hypothesis 2). Moreover, we have also the following expectations: People using their AMs for self‐continuity purposes will be more active on Facebook in sharing information about their life events then people moved by social‐bonding or directive‐behavior function of AMs, coherent with prior works (i.e., Seyfi & Soydaş, ; Caci et al, ; Hypothesis 3). The relationship among all the three functions of AMs and the amount of textual or visual information about life events would be stronger for women than for men, consistent with literature (e.g., Vranic et al, 2018; Mendelson & Papacharissi, ; Hypothesis 4). The relationship among all the three functions of AMs and the amount of textual or visual information about life events would be stronger for middle‐aged than young adult people, considering that nowadays middle‐aged people are more involved then young in using Facebook (Bosak & Park, ; Hypothesis 5). The relationship among all the three functions of AMs and life events with positive themes would be stronger for middle‐aged than for young adult women (Hypothesis 6). …”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…We expect to found a definite influence of demographic variables such as gender and age in the association between functions of AMs and Facebook usage (Hypothesis 2). Moreover, we have also the following expectations: People using their AMs for self‐continuity purposes will be more active on Facebook in sharing information about their life events then people moved by social‐bonding or directive‐behavior function of AMs, coherent with prior works (i.e., Seyfi & Soydaş, ; Caci et al, ; Hypothesis 3). The relationship among all the three functions of AMs and the amount of textual or visual information about life events would be stronger for women than for men, consistent with literature (e.g., Vranic et al, 2018; Mendelson & Papacharissi, ; Hypothesis 4). The relationship among all the three functions of AMs and the amount of textual or visual information about life events would be stronger for middle‐aged than young adult people, considering that nowadays middle‐aged people are more involved then young in using Facebook (Bosak & Park, ; Hypothesis 5). The relationship among all the three functions of AMs and life events with positive themes would be stronger for middle‐aged than for young adult women (Hypothesis 6). …”
Section: Introductionsupporting
confidence: 89%
“…• The relationship among all the three functions of AMs and the amount of textual or visual information about life events would be stronger for middle-aged than young adult people, considering that nowadays middle-aged people are more involved then young in using Facebook (Bosak & Park, 2018; Hypothesis 5).…”
Section: The Current Studymentioning
confidence: 98%
“…Social support from family and peers is one key component of health behaviour change including weight management 8–12 . In the past decade, researchers have attempted to harness social networking sites for healthy lifestyle interventions both as the sole means of intervention delivery 13 or to provide additional social support to participants via coach and peers 14–19 …”
Section: Introductionmentioning
confidence: 99%
“…7 Social support from family and peers is one key component of health behaviour change including weight management. [8][9][10][11][12] In the past decade, researchers have attempted to harness social networking sites for healthy lifestyle interventions both as the sole means of intervention delivery 13 or to provide additional social support to participants via coach and peers. [14][15][16][17][18][19] A recent review of social media use in behaviour change interventions found that functions for peer grouping improved perceptions of social support and social support coping.…”
Section: Introductionmentioning
confidence: 99%
“…Among other things, the skewed distribution is probably due to the fact that the advertisement targeted subjects searching for or "liking" skin products. Even though studies have shown that the age of adults using Facebook is 18-65 years (mean 48.2 years) [27], future studies using online recruitment should be aware of this and consider advertising through other channels than via social media. For example, using websites of patient associations or pharmacies to target the elderly, to reduce bias in recruitment.…”
Section: Plos Onementioning
confidence: 99%